Analisis Kinerja Sub Terminal Agribisnis Kutabawa (Studi Kasus pada Pemasaran Sayuran Bawang Daun, Petsai dan Caisim di Desa Kutabawa, Kecamatan Karangreja, Kabupaten Purbalingga) - Khomsiah, Khomsiah; M, Alpha Nadeira; Widyarini, Indah (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2021)
STA Kutabawa is a market established by the local government of Purbalingga to facilitate the marketing of agricultural commodities in kutabawa village and its surroundings. Even though STA has been operating for a long time, there are still traditional marketing institutions in Kutabawa Village.this shows that farmers in this village have not all used STA as a means to market their agricultural products.This study aims to 1) analyze the performance of the Kutabawa Agribusiness Sub-Terminal and 2) Analyze the farmers' choice opportunities in choosing marketing institutional and their reasons. Sampling of 56 farmers was obtained using the simple random sampling method and as many as 37 marketing institutions were obtained using the snow ball sampling method. STA performance analysis methods used are marketing channels, marketing margins, farmer's share and profit-to-cost ratios, and opportunities for marketing institutional choices using binary logistic regression. The results showed that 1) The performance of the Kutubawa Agribusiness Sub-Terminal shows that there are differences in marketing margins, farmer share and profit-to-cost ratios for each marketing channel through the Kutabawa STA and traditional institutions. Marketing channels through the Kutabawa STA are more efficient than traditional institutions, because they have lower marketing margins, prices received by farmers is higher and each marketing institution get the benefits from the marketing costs incurred. 2) Opportunity to choose it as a place of payment, sales volume, land distance to STA and vehicle ownership. Opportunities for farmers who requested directly, the number of harvests is less than equal to 140 kilograms, planting distance is less than two kilometers and has a vehicle that uses to choose directly to Kutabawa STA.